In the Footsteps of Scribonius Largus, a Pioneer of Clinical Pharmacy in Ancient Rome - Christos Tsagkaris; Anna Loudovikou; Dimitrios V. Moysidis; Andreas S. Papazoglou; Konstantinos Kalachanis (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Clinical pharmacy involves pharmacists in direct patient care concerning optimizing medicines and promoting health awareness and disease prevention. The whereabouts of the field can be traced to Scribonius Largus, a renowned physician and pharmacist in ancient Rome. Although Largus served as an imperial physician, he has also been an exemplary pharmacist authoring a comprehensive pharmacognosy textbook and dedicated a big part of his life to improving pharmacotherapy and advancing ethics in the field. Revisiting his contributions provides valuable lessons for contemporary clinical pharmacists.